Teaching Information Literacy in University Libraries in Kenya during the COVID-19 Pandemic - Sawe, Emily; Musangi, Penninah (KLISC Journal of Information Science and Knowledge Management, 2023)
Kenya detected its first COVID-19 case on March 19th, 2020, which led to educational institutions being shut down and learning activities shifting online. This change greatly impacted university operations, including university libraries. Before the pandemic, university libraries were teaching information literacy (IL) through conventional methods, which were mostly physical. Universities transitioning to online education necessitated libraries to rethink IL instruction. The purpose of this study is to assess the suitability of the modes of teaching, librarian skills, and resources required for IL delivery in university libraries in Kenya during the COVID-19 period. The objectives are to establish the modes of teaching IL used by university libraries, the skills, and resources required in the teaching of IL in an online environment, identify the challenges faced to offer IL during the COVID-19 pandemic period and recommend the best practices in IL delivery in an online environment. The study used systematic review of existing literature. Multi-platforms, synchronous and asynchronous, were employed at varied degrees; the success of the online modes of teaching was affected by the inaccessibility of the requisite resources, unpreparedness by the librarians and students as well as the demand for new skills. The study recommends contextualization of teaching initiatives, provision of professional development to librarians, development of contingency plans, and evaluation of the online modes of teaching for continual improvement
Keywords: COVID-19; information literacy; university libraries